TELAAH TERHADAP PENERAPAN PANDUAN RANCANG KOTA KAWASAN CIKINI PADA SUB KAWASAN 5 DAN 6 - Suteja, Mekar Sari; Stefani; Setiawan , Jennifer; Veronica , Adinda; Amnah; Cindy , Birgitta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
The Cikini area in Menteng District, Central Jakarta is one of the areas that is expected to become an urban tourism magnet in Jakarta. This area has been planned to become an urban art center and creative hub area with several potential tourist attractions such as historical buildings, educational and cultural buildings, as well as various arts programs. According to Regional Spatial Planning Regulation (RTRW) for DKI Jakarta Province 2030, this area has been designated as one of the central system activities of the Central Jakarta Administrative City. However, the Cikini area still has the spatial characteristics of its old area. There are many places with memories which are still exist today. The issuance of the Draft Law Nusantara National Capital (IKN) has had an impact on changing the function of the City of Jakarta from The capital becomes the Special Region of Jakarta. The relocation of the capital must be adapted to developments occurring in the spaces of the city of Jakarta, including the Cikini area. An actual Urban Design Guidelines (UDGL) must also be evaluated every 5 years. Since the enactment of Gubernatorial Regulation No. 98 of 2020 concerning the UDGL Cikini, it has been 3 years since the plan was implemented and its realization should be monitored. Through descriptive-analytical-comparative methods, the Community Service team tries to see the real conditions and problems that exist in the field. It is hoped that this Community Services can help the Government to see and observe directly changes and developments in the Cikini area so that it can become evaluation material for the revision of the 2025 Cikini Urban Design Guideline.